Climate–vegetation control on the diurnal and seasonal variations of surface urban heat islands in China - Decheng Zhou; Liangxia Zhang; Dan Li; Dian Huang; Chao Zhu (Environmental Research Letters, 2016)
Remotely sensed surface urban heat islands (UHIs) have gained considerable interest in recent decades due to the easy access and the wall-to-wall coverage of satellite products. The magnitude or intensity of surface UHIs have been well documented at regional and global scales, yet a systematic evaluation of the temporal variability over large areas is still lacking. In this study, the diurnal and seasonal cycles of surface UHI intensities (SUHIIs) in China are examined using Aqua/Terra MODIS data from 2008 to 2012. Results show that the mean annual SUHIIs varied greatly in a diurnal cycle, characterized by a positive day-night difference (DND) in Southeast China and the opposite in Northeast and Northwest China. Also, the SUHIIs differed dramatically in a seasonal cycle, indicated by a positive summer-winter difference (SWD) in the day and a negative SWD at night, accompanied by the highly diverse DNDs across seasons and geographic regions. Northwest and Northeast China overall showed the largest DND and SWD (>3 °C), respectively. These diurnal and seasonal variations depend strongly on local climate-vegetation regimes, as indicated by a strong positive correlation between DND and precipitation (and air temperature) and a negative relationship between DND and vegetation activity across cities and seasons. In particular, SHUIIs were quadratically correlated with the mean annual precipitation across space, suggesting that there might be a threshold in terms of the effects induced by local background climate. Our findings highlight the importance of considering the temporal variability of UHIs for more accurate characterization of the associated ecological and social-economic consequences.